The PTPN2/PTPN1 inhibitor ABBV-CLS-484 unleashes potent anti-tumour immunity - Baumgartner, Christina K.; Ebrahimi-Nik, Hakimeh; Iracheta-Vellve, Arvin; Hamel, Keith M.; Olander, Kira E.; Davis, Thomas G. R.; McGuire, Kathleen A.; Halvorsen, Geoff T.; Avila, Omar I.; Patel, Chirag H.; Kim, Sarah Y.; Kammula, Ashwin V.; et al. (Nature (London), 2023)
Immune checkpoint blockade is effective for some patients with cancer, but most are refractory to current immunotherapies and new approaches are needed to overcome resistance 1 , 2 . The protein tyrosine phosphatases PTPN2 and PTPN1 are central regulators of inflammation, and their genetic deletion in either tumour cells or immune cells promotes anti-tumour immunity 3 – 6 . However, phosphatases are challenging drug targets; in particular, the active site has been considered undruggable. Here we present the discovery and characterization of ABBV-CLS-484 (AC484), a first-in-class, orally bioavailable, potent PTPN2 and PTPN1 active-site inhibitor. AC484 treatment in vitro amplifies the response to interferon and promotes the activation and function of several immune cell subsets. In mouse models of cancer resistant to PD-1 blockade, AC484 monotherapy generates potent anti-tumour immunity. We show that AC484 inflames the tumour microenvironment and promotes natural killer cell and CD8 + T cell function by enhancing JAK–STAT signalling and reducing T cell dysfunction. Inhibitors of PTPN2 and PTPN1 offer a promising new strategy for cancer immunotherapy and are currently being evaluated in patients with advanced solid tumours (ClinicalTrials.gov identifier NCT04777994 ). More broadly, our study shows that small-molecule inhibitors of key intracellular immune regulators can achieve efficacy comparable to or exceeding that of antibody-based immune checkpoint blockade in preclinical models. Finally, to our knowledge, AC484 represents the first active-site phosphatase inhibitor to enter clinical evaluation for cancer immunotherapy and may pave the way for additional therapeutics that target this important class of enzymes. An orally bioavailable small-molecule active-site inhibitor of the phosphatases PTPN2 and PTPN1, ABBV-CLS-484, demonstrates immunotherapeutic efficacy in mouse models of cancer resistant to PD-1 blockade.